Peran Penggunaan Birthing Ball Selama Kala I Fase Aktif Terhadap Kemajuan Persalinan dan Kepuasan Ibu: Systematic Review - Nur Hidayah MS; Syarifah Masita; Amina Ahmad; Kartini Kartini (Madu Jurnal Ilmu Kebidanan, 2026)
Prolonged labor during the active phase of the first stage can increase the risk of complications for both the mother and the baby. One of the non-pharmacological complementary treatments considered to accelerate the labor process and make childbirth more enjoyable for mothers, the Birthing ball still requires systematic evidence to ensure that it can be applied in midwifery practice. The objective of this research is to systematically analyze the role of the Birthing ball on the progress of labor during the active phase of the first stage and the positive experience of mothers in labor (satisfaction). The research design follows the PRISMA protocol thru a comprehensive review. For articles published from 2015 to 2025, a literature review was conducted using the Google Scholar, Scopus, and PubMed databases. Inclusion criteria included experimental studies discussing the use of a Birthing ball intervention for mothers in the active first stage of labor, with outcomes measuring labor duration and maternal satisfaction. Ten selected articles were qualitatively synthesized. The synthesis results show that the use of a Birthing ball significantly accelerates the duration of the first stage of active labor (on average 1.5–2 hours faster) thru the optimization of fetal position and gravitational force. In addition, this intervention consistently improves maternal satisfaction scores and reduces the intensity of functional pain, providing a greater sense of control during the labor process. The Birthing ball is effective in optimizing the clinical progress of labor and the psychological well-being of the mother. Midwives are advised to integrate this method as a complementary care standard to achieve a positive childbirth experience.